Captain America. Vol. 1, Winter in America - Coates, Ta-Nehisi (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2019)
In the aftermath of Hydra's takeover of the nation, Captain America becomes a controversial figure with nowhere to turn for aid in stemming the rise of the influence brokers known as the Power Elite.